Angels & Demons - Brown, Dan (New York Pocket Star Books, 2001)
An ancient secret brotherhood. A devastating new weapon of destruction. An unthinkable target. World-renowned Harvard symbologist Robert Langdon is summoned to a Swiss research facility to analyze a cryptic symbol seared into the chest of a murdered physicist. What he discovers is unimaginable: a deadly vendetta against the Catholic Church by a centuries-old underground organization -- the Illuminati.
Keywords: Vatican City -- Illuminati -- Papacy